Manual Vacuum Aspiration in IUFD 18 Weeks - Brahmana, Ivanna Beru (Universitas Muhammadiyah Yogyakarta, 2021)
Manual Vacuum Aspiration (MVA) is an action to evacuate the uterine cavity up to 14 weeks gestation. In a more extensive pregnancy, it is worried that the action of the MVA is less clean so that it will still repeat the action of sharp curettage.Â This article reports a multigravida aged 42 years old, G5P2A2, intrauterine fetal death (IUFD) at 18 weeks, undergoing MVA. Diagnosis of IUFD was performed using ultrasound examination. Before MVA was done, the patient was previously given 100 Î¼g of misoprostol orally for dilation. This pregnancy was the third pregnancy with a second husband, all of whom had abortions. Manual Vacuum Aspiration had a minimal risk of uterine injury. After MVA was conducted, ultrasound examination was repeated to confirm a clean uterine cavity. It had been carried out on an indication of IUFD of 18 weeks gestation with the result of a clean uterine cavity and minimal bleeding. Furthermore, Post-Abortion Intra-Uterine Device (PAIUD) was installed adequately, not causing complaints. Based on the result, it can be concluded that MVA is effective for evacuation of uterine cavities on 18 weeks gestation.